Acute uncomplicated cystitis: is antibiotic unavoidable?. Issue 9 (September 2018) - Kulchavenya, Ekaterina
Background: Acute uncomplicated cystitis in women is one of the most frequently diagnosed bacterial infections. Methods: In a pilot, open, noncomparative prospective study, 29 nonpregnant, sexually active women with acute uncomplicated cystitis were enrolled. The mean age was 28.9 ± 4.3, range 22–36 years. All patients received unique therapy: the nonsteroidal anti-inflammatory drug (NSAID) ketoprofen, 100 mg once a day for 5 days, and Canephron, 2 dragees three times a day for 1 month. Results: In 2 days, four patients (13.8%) had no tendency to improvement; they were considered as nonresponders and antibiotics were prescribed for them. The remaining 25 patients (86.2%) showed significant improvement and were considered as responders; they continued the therapy with ketoprofen and Canephron. In 7 days, 21 patients (72.4%) had no dysuria and leucocyturia; they were considered as fast responders to phytotherapy. In four patients (13.8%), after 7 days of therapy insignificant dysuria and leucocyturia were found; they were considered as slow responders to phytotherapy. All 25 patients continued the intake of Canephron for 1 month to prevent a relapse. When treatment finished, all patients were well. In 6 months, no relapses were diagnosed. Conclusion: The majority (86.2%) of young, nonpregnant women with acute uncomplicated cystitis were cured by 30 days of phytotherapy combined initially (5 days) with the NSAID ketoprofen; an antibiotic was indicated in only 13.8% of patients. Patients with acute uncomplicated cystitis may be divided into three subgroup: nonresponders to phytotherapy; slow responders to phytotherapy; fast responders to phytotherapy. Antibiotic therapy is indicated in nonresponders, but slow and fast responders may be treated without an antibiotic, by phytotherapy with an initial short course of an NSAID only.